Assessment On The Performance Of Asphalt Mixtures Prepared With Adhesion Promoters - Nge, Jia Sheng (Universiti Sains Malaysia, 2019)
Asphalt pavement is typically susceptible to moisture damage and is less durable compared to concrete pavement. However, the performance of the asphalt pavement could be improved with the incorporation of additives or modifiers thru binder modifications. The objective of the study is to assess the effect of adhesion promoters, namely PBL and M5000 onto the Hot Mix Asphalt (HMA). The performance has been assessed in terms of the service characteristics, the bonding properties and the mechanical performances. The service characteristics were assessed using Workability Index (WI) and Compaction Energy Index (CEI) to show the ease of asphalt mixture to be mixed and compacted to the desired density. The bonding properties of the modified asphalt mixtures were determined using the boiling water test and static test method to indicate the degree of coating after undergoing specific conditioning time and temperature. The mechanical performances of the modified asphalt mixture were evaluated by Marshall stability, Leutner shear, semi-circular bending and Modified Lottman tests. All specimens were prepared by incorporating adhesion promoters at the dosage rates of 0.5% and 1.0% by weight of asphalt binder for both additives. From the investigation, the bonding properties were significantly improved for the modified asphalt mixture compared to the control mixture. The WI of the modified asphalt mixture was increased and the CEI was decreased in comparison to the control specimen, which means the workability of the modified asphalt mixture is higher and requires less energy to be compacted. Modified asphalt mixture generally had better performance in most of the mechanical performances except the Leutner shear test result. The control specimen achieved a higher shear strength than the PBL at both dosages. While the M5000 at 0.5% had higher shear strength than the M5000 at 1.0% dosage and the control specimen. Therefore, the modified asphalt mixtures have better overall performance than the control mix. Overall, the modified asphalt mixture is more moisture resistant and durable against severe weather condition and traffic loadings.